Physio-chemico-thermo-mechanical properties of selected biodegradable polymers. Issue 3 (1st September 2013) - Priyodip, P.; Balaji, S.; Vijaya Kini Kini, M. M. Vijaya
Abstract : Polymers from renewable resources recently attracted research community mainly because of environmental concerns, low cost, availability and their biodegradability after usage. However, the intrinsic deficiencies of natural biopolymers, including poor mechanical properties, poor water resistance and difficult processability limit their use. The analysis presented here, is on renewable, bio-based resins for their mechanical, morphological, thermal and hydrolytic properties. The resins were prepared from starch, cellulose, lignin, chitosan, gelatin and their derivatives. All these matrices had good thermoplastic and mechanical properties. Among these blends, a representative starch-based specimen had maximum load bearing capacity 118·17 N on tensile stress of 1·97 MPa and modulus 221·36 MPa. In case of lignin, maximum load bearing capacity was 19·96 N on tensile stress of 0·44 MPa and modulus 287·11 MPa. In chitosan, maximum load bearing capacity was 74·03 N on tensile stress of 1·68 MPa and modulus 372·35 MPa. In case of gelatin, maximum load bearing capacity was 46·43 N on tensile stress of 1·22 MPa and modulus 829·75 MPa. Mechanical strength based on modulus showed: gelatin > chitosan > lignin > starch > cellulose. Thermal withstanding trend (dry heat) showed: gelatin > lignin > chitosan > cellulose > starch, whereas moist heat showed: gelatin > lignin > starch > chitosan > cellulose. Microscopic observations and biodegradability is also discussed.